2020
DOI: 10.2139/ssrn.3685915
|View full text |Cite
|
Sign up to set email alerts
|

The Brussels Effect in Action: Do the EU’s Standards Travel Abroad? A Study on Control Systems for Geographical Indications in the EU and Thailand

Abstract: o a d s o f Tr a d e , D e v e l o p m e n t, a n d C u lt u r e. F o c u s o n A s i a-Pa c i f i c 344-346, (I. Calboli & N.-L. Wee-Loon eds., 2017); I. Calboli, Geographical Indications between Trade, Development, Culture, and Marketing: Framing a Fair(er) System of Protection in the Global Economy?, in G e o g r a p h i c a l I n d i c at i o n s b e t w e e n Tr a d e , D e v e lo p m e n t, a n d C u lt u r e. F o c u s o n A s i a-Pa c i f i c 22, (I. Calboli & N.-L. Wee-Loon eds., 2017).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Bradford (2020) asserts that for the 'Brussels Effect' to occur, five conditions need to be cumulatively met. However, follow-up research has found that in practice it can occur in the absence of some criteria being fulfilled (Preusse et al, 2020). Bradford's five conditions for the 'Brussels Effect' are: sufficient market size, regulatory capacity, stringent standards, inelastic targets, and non-divisibility.…”
Section: Eu Regulatory Processmentioning
confidence: 99%
“…Bradford (2020) asserts that for the 'Brussels Effect' to occur, five conditions need to be cumulatively met. However, follow-up research has found that in practice it can occur in the absence of some criteria being fulfilled (Preusse et al, 2020). Bradford's five conditions for the 'Brussels Effect' are: sufficient market size, regulatory capacity, stringent standards, inelastic targets, and non-divisibility.…”
Section: Eu Regulatory Processmentioning
confidence: 99%
“…In order for the 'Brussels Effect' to take hold it must be underpinned by 5 elements that other jurisdictions do not have to the extent that the EU does (Bradford 2020). While Bradford implies that for the 'Brussels Effect' to occur these conditions need to be cumulatively met, follow-up research has found that in practice the effect occurs with only some of the criteria being fulfilled (Preusse et al, 2020). Bradford's five conditions for the 'Brussels Effect' are: market size, regulatory capacity, stringent standards, inelastic targets, and non-divisibility.…”
Section: Eu Regulatory Processmentioning
confidence: 99%
“…Despite the anticipation of such effects, the EU has long been interested in the gradual export of its sanitary and phytosanitary standards, including animal welfare standards. It is widely recognized that animal welfare is a domain in which a strong Brussels effect has been generated (Preusse et al, 2020), although it has not been subject to systematic empirical analysis. The "Brussels effect" connotes a de facto pressure toward high standards by which businesses employ the same (high) standards also in jurisdictions outside of those standards formally applied (Bradford, 2021).…”
mentioning
confidence: 99%